The need for stronger international support to integrate health and well-being and transform education: a perspective on developing countries - Abduvahobov, Parviz; Cameron, Stuart J.; Ibraheem, Ayodeji; Herat, Joanna; Castle, Christopher (Frontiers in Public Health, 2024)
The reciprocal relationship between education and health is well-established, emphasizing the need for integrating health, nutrition, and well-being components into educational sector planning. Despite widespread acknowledgment of this need, countries lack concrete measures to achieve this integration. We examine challenges that countries have faced and the progress they have made in integrating these components into education sector plans and review the extent to which existing educational planning guidelines and tools address health and well-being. The review reveals a significant underrepresentation of health, well-being, and related themes in existing educational planning frameworks. Recent tools and frameworks developed to support a more holistic approach to education have not yet been widely adopted in standard education sector planning processes. The implementation of such approaches remains inconsistent, with significant barriers including limited cross-sectoral collaboration, lack of capacity, and insufficient funding, among others. Addressing these gaps requires improved guidance, technical support, and a multisectoral approach to education planning that includes health, nutrition, and well-being as fundamental components of foundational learning, supported by political commitment, capacity, and adequate financing.